Pengaruh Kepribadian, Kemampuan Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Suryamas Citra Lestari Cabang Surakarta - Santoso, Wahyu Aji; , Dr. Rini Kuswati, S.E., M.Si (2016)
The purpose of this study was to investigate the influence of personality, ability and discipline on employee performance. The population of this research at PT. Suryamas Citra Lestari Surakarta branch. Processing of data by means of SPSS. The results of the t test variable personality, ability and discipline have an influence on employee performance. Test f show together variable personality, ability and discipline affect the performance. The coefficient of determination of 67.6% means that employees are able to work variable explained by personality, ability and discipline of work and the remaining 32.4% is explained by other variables outside the study.